Automotive policy and the restructuring of the south african industry, 1990 - 2005. - Black, Anthony (Department of Philosophy, 2024)
Since 1990 the South African automotive industry has been through the most dramatic phase of its long history as reduced protection has led to much greater international integration. This thesis analyses the restructuring of the sector in response to these developments. The first major section provides a detailed assessment of the international environment and its impact on the prospects for growth of the automotive industry in developing countries and South Africa in particular. In many developing countries, the sector has been subject to extensive state support and intervention. While traditional production locations in advanced countries remain dominant, there has been a significant shift of production to developing countries. This expansion has, however, been focused on a relatively small number of locations. For countries which do not have very large existing or potential domestic markets, policy needs to define an 'automotive space' and provide some protection to anchor the domestic industry if local capacity is to be retained and developed. In South Africa, a gradual but sustained period of tariff liberalisation has been coupled with import-export complementation measures aimed at increasing exports and achieving a higher degree of specialisation. With its unfavourable geographical location and history of heavy protection, the prognosis for the South African industry in the early 1990s was not good. To date the costs of liberalisation have been quite low. The export response to the realignment of the incentive structure has been strong and the industry has become much more efficient and competitive. However, other objectives have not been achieved. Recently, the share of vehicle imports has grown sharply. Local content levels remain low partly because of lower protection. There have also been serious distortions. The system of export credits used to offset import duties has led to rapid expansion of 'peripheral' component exports, driven more by the objective of rebating import duties than any real economic justification. Investment levels have been modest compared to the investments flowing into some of the world's more dynamic emerging automotive industries. Historically, the development of small-scale, multi-model plants has been the central structural problem in the South African automotive industry. It exacerbated the lack of competitiveness associated with high levels of protection and limited the prospects for expanding local content. One of the key objectives of policy has been to encourage industry rationalisation. But while a theoretical case for industrial policies can easily be made, implementation is much more complex. There has been progress in achieving higher model volumes, but it has not been sufficient to justify investments in high levels of local content. A number of case studies of firm level restructuring were conducted. These illustrate that the major reason for the lack of competitiveness in the initial stages was not necessarily inefficiency or a lack of dynamism on the part of firms but rather an inefficient industry structure consisting of too many low volume producers. Component firms have in fact proved quite dynamic in adapting to this environment. Restructuring has taken a number of forms and firms have proved remarkably resourceful. But internal or plant level changes, while necessary have seldom proved sufficient. In many cases firms have been forced to seek out a foreign partner. Foreign ownership or control in turn has had a number of effects on firm performance and prospects in areas such as exports, R&D and the use of domestic suppliers. The industry has made substantial progress towards developing a more efficient and competitive structure. But difficulties remain as it attempts to attract investment in an increasingly competitive international environment. The scale of domestic production is still not sufficient to encourage high levels of localisation of components. That in turn means that assembly sector costs remain high because of the logistics costs associated with high import levels. The challenge for policy currently is to encourage investment in high volume, sustainable automotive production while at the same time gradually moving to more neutral and lower levels of support.